Characterization of Xylose Uptake in the Yeasts Pichia heedii and Pichia stipitis - Does, Amy L. (1989)
The kinetics of xylose uptake were investigated in the efficient xylose fermenter Pichia stipitis and in the more readily genetically manipulated, strictly respiratory yeast Pichia heedii. Both yeasts demonstrated more than one xylose uptake system, differing in substrate affinity. The K(m) of high-affinity xylose uptake in both organisms was similar to that of the efficient high-affinity glucose uptake system of Saccharomyces cerevisiae. In P. heedii, low-affinity xylose uptake was enhanced with growth on 2% but not 0.05% xylose and high-affinity uptake was reduced. In contrast to glucose uptake, xylose uptake in P. heedii was inhibited by dinitrophenol. Dinitrophenol inhibited both glucose and xylose uptake by P. stipitis. Glucose uptake was not inhibited by a 100-fold molar excess of xylose in P. heedii. It is suggested that xylose uptake in P. heedii is via a carrier system(s) distinct from those for glucose uptake.